Assessment and Retrieval of Aspirated Tracheoesophageal Prosthesis in the Ambulatory Setting - Karuna Dewan; Andrew Erman; Jennifer L. Long; Dinesh K. Chhetri (Case Reports in Otolaryngology)
Tracheoesophageal prosthesis (TEP) is the most common voice restoration method following total laryngectomy. Prosthesis extrusion and aspiration occurs in 3.9% to 6.7% and causes dyspnea. Emergency centers are unfamiliar with management of the aspirated TEP. Prior studies report removal of aspirated TEP prostheses under general anesthesia. Laryngectomees commonly have poor pulmonary function, posing increased risks for complications of general anesthesia. We present a straightforward approach to three cases of aspirated TEP prosthesis removed in the ambulatory setting. In each case, aspirated TEP was diagnosed with flexible bronchoscopy under local anesthesia at the time of consultation, and all prostheses were retrieved atraumatically using a biopsy grasper forceps inserted via the side channel of the bronchoscope. The aspirated TEP prosthesis can be safely and efficiently removed via bedside bronchoscopy.